Evaluating the content and organizing it in the Arabic language curriculum for the seventh grade of basic education in Libya from the point of view of specialists (مجلة جامعة سرت للعلوم الانسانية, 2024)
This research aimed to evaluate and organize the content in the Arabic language curriculum for the seventh grade of basic education in Libya from the point of view of specialists. The researchers used the descriptive approach to collect data by using a questionnaire that was prepared and judged. It was then distributed to a community sample of (121) teachers and (9) inspectors, and the research reached the following results:1- Evaluating the content of the Arabic language curriculum for the seventh grade of basic education in Libya; It was at a moderate degree level, but it did not reach the required level.2- The evaluation of the organization of the content of the curriculum referred to was It was at a moderate degree level and did not rise to the required level according to the estimates of specialists.3- There are statistically significant differences between the level of average ratings of the two samples of teachers and inspectors on the two axes of content and organization in favor of the sample of teachers.
Keywords: curriculum evaluation; Arabic language curriculum evaluation; content evaluation; content organization, seventh grade